TEST OF ANTIBACTERIAL ACTIVITY FROM THE COMBINATION OF ETHANOL EXTRACT OF WARU (HIBUSCUSTILIACEUS L.) LEAVES AND LEAF RED PUCUK (SYZYGIUM OLEANA) AGAINST SALMONELLA THYPI ON 2021 - Purba, Novandi; Putri, Nabila (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The research in this paper aims to determine the effectiveness of immunostimulants from ethanol extract of coffee parasite leaves (Loranthus ferrugineus Roxb) with four variants of doses of 50mg / kgBB, 100mg / kgBB, 200mg / kgBB, 400mg / kgBB. This study used 18 male white rats with 200 gram BB which were divided into 6 treatment groups. Rats were injected with 0.1ml SDMS 1% for 7 consecutive days intraperitoneal, then on the 7th day each blood sample was taken through veins in the tail, CMC Na 0.5% suspension, and Levamisole suspension 50mg / kgBB as a positive control was administered orally on the 8th day. Then blood samples were collected in a micro tube and then 1900rpm was centrifuged at a temperature of 4oC for 10 minutes. The results of the study of ethanol extract of coffee parasite leaves proved effective as immunostimulants because they have a value close to positive control, starting from a dose of 200mg / kgBB to 400mg / kgBB.